Soviet Impact on the Western World - Carr, Edward Hallett (London, 1947)
The six chapters of this small volume have their origin in six lectures delivered in Oxford in February and March, 1946, for the Estlin Carpenter Trust and printed here without substantial change. A considerable part of Chapter I was also included in the Cust Foundation Lecture delivered in November, 1945, at University College, Nottingham, on "Democracy in International Affairs" and published in pamphlet form by the College. The author is indebted to the College for courteous per mission to reprint this material in the present volume.
Keywords: Foreign Relation